Rheological study on lower critical solution temperature behavior of organo-soluble cyano-substituted p-aramid in isotropic phase - Kim, Hyo Jeong; Thanakorn, Yeamsuksawat; Jung, Dae Eon; Eom, Youngho (Korea-Australia rheology journal, 2024)
Poly(2-cyano- p -phenylene terephthalamide) (CY-PPTA) has garnered significant interest as a promising precursor for super p -aramid fibers because of its organosolubility in N , N -dimethyl acetamide/lithium chloride (DMAc/LiCl) while conserving the superior properties of the resultant fibers. However, CY-PPTA has been reported to exhibit abnormal phase behavior owing to the strong dipole–dipole interactions induced by the cyano groups. Herein, we rheologically study the isotropic phases of CY-PPTA/DMAc solutions with respect to the concentration and temperature and compare them with those of CY-PPTA/sulfuric acid (H 2 SO 4 ) solutions. In the isotropic region, the CY-PPTA solutions yield a higher power-law exponent of the dynamic viscosity ( η' ) versus concentration of 6.0 ( ηʹ ~ c 6.0 ) in the DMAc system than that in H 2 SO 4 ( ηʹ ~ c 3.2 ). Moreover, the CY-PPTA/DMAc solutions exhibit a lower critical solution temperature (LCST) behavior with increasing temperature, in contrast with the upper critical solution temperature in H 2 SO 4 . Consequently, the viscosity and exponent of the CY-PPTA/DMAc solutions increase at elevated temperatures. As shown by the Cole–Cole plot, the heterogeneity in the DMAc system becomes worse. The LCST of the CY-PPTA solution is ascribed to the intermolecular interactions between the highly polar cyano groups, which are negligible in H 2 SO 4 .